POTRET PEMBELAJARAN KIMIA DI SMA: ANALISIS PROSES PEMBELAJARAN DI KELAS - -, Yara Qumarani; Coryna Oktaviani (Universitas Samudra, 2024)
This research aims to analyze the chemistry learning process at Unggul Cut Nyak Dhien High Schoolin Langsa city, with a focus on the techniques used by teachers and student involvement in theteaching and learning process. The method used in this research is a qualitative descriptive approach,which collects data through observation, interviews with teachers and students, and documentation.The research results show that although the use of PowerPoint as a medium for delivering material isquite helpful, the learning process tends to be one-way, with most students involved in limitedquestions and answers. More active students often dominate, while most others are passive. Apartfrom that, the lack of practical activities also limits students' understanding of more complex chemicalconcepts. This research suggests that learning methods should be updated with more experiments andopportunities for students to ask questions, to increase their engagement and understanding of thematerial being taught.